Ações pública e privada no processo de ocupação de Ribeirão Preto: do núcleo Antônio prado a atuação do GDU Grupo de Desenvolvimento Urbano - Melo, Rose Elaine Borges de (2017)
The work studies the performance of the different agents of the real estate market in the process of occupation of the South sector, located in the geographical periphery of the Ribeirão Preto´s City, from 1990 to 2010. The study was based on the analysis of the actions of the productive agents of the real estate market, especially the UDG Urban Development Group (association of builders, developers and land owners) and actions of the municipal public power as a regulator of urban space. In this way, we analyze: the legislation through the urbanistic instruments of control of land use and occupation; Programs, urban projects and master plans through the concepts and guidelines used in the production and organization of urban space (occupation pattern, growth guidelines and urban structure); Public services through the implementation of infrastructure and urban equipment; And, allotments and condominiums horizontal and vertical through the projects approved in the Secretariat of Planning and Public Management of Ribeirão Preto. The results verify the hypotheses that guided the accomplish of this research: 1) in addition to socioespatial segregation center periphery, from its beginnings, the process of formation and expansion of Ribeirão Preto´s City presents a pattern of occupation where the high income population predominates in the southern region and the population of Low income in the north of the city 2) real estate agents such as developers, real estate developers and landowners, among others, acted in an organized way in the process of occupation of the South sector, located in the geographical periphery of the city of Ribeirão Preto, in the Period from 1990 to 2010 becoming the effective planners of this urban space.